2014
DOI: 10.3109/01676830.2014.904377
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve for use of the Sonopet Ultrasonic Aspirator in Endoscopic Dacryocystorhinostomy

Abstract: The Sonopet Ultrasonic Aspirator Universal handpiece can be used safely and effectively for eDCR surgery. A significant learning curve exists for adoption of this technology. Appropriate handpiece tip selection and machine setting adjustments are crucial for successful adoption of this technology and avoidance of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Chappell et al demonstrated that the mean surgical time using an UBA decreased by approximately 36% after the first quartile of cases, as the surgeon developed familiarity with the device. 13 An ideal setting for this tool may be a high-volume, tertiary care center where surgical time savings are valuable and the device may be shared among surgeons from multiple specialties such as otolaryngology, oral and maxillofacial surgery, and neurosurgery. Furthermore, given its potential benefits to patient safety, a teaching hospital with residents and fellows may be an ideal environment to implement this tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chappell et al demonstrated that the mean surgical time using an UBA decreased by approximately 36% after the first quartile of cases, as the surgeon developed familiarity with the device. 13 An ideal setting for this tool may be a high-volume, tertiary care center where surgical time savings are valuable and the device may be shared among surgeons from multiple specialties such as otolaryngology, oral and maxillofacial surgery, and neurosurgery. Furthermore, given its potential benefits to patient safety, a teaching hospital with residents and fellows may be an ideal environment to implement this tool.…”
Section: Discussionmentioning
confidence: 99%
“…A potential limitation to its adoption in an oculoplastic practice is the current high cost of the device (approximately $100,000) and its disposable, single-use hardware ($350). 13 This study was limited by its retrospective design and small sample size, which influenced the power of statistical analyses. Furthermore, given the shorter length of postoperative follow-up in this study, late surgical failures may not have been detected despite meticulous communication of return precautions with all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the endoscopic laser approach was faster, its lower success negates the apparent time benefit it offers. Chappel et al 10 studied the learning curve with the use of an ultrasonic aspirator in 26 endoscopic DCRs. They reported a decrease in surgical time by 36.4% and 33.9% in unilateral and bilateral surgeries, respectively, as the experienced increased, which subsequently reached a plateau of 67.2 and 80.7 minutes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…2,[5][6][7][8] Mechanical burrs are popular and commonly used for quick removal of the superior bone; however, ultrasonic emulsification is fast emerging as an alternative and safe powered instrument, although there is limited data on the surgical outcomes using the ultrasonic instruments. 6,[8][9][10] Few studies in the past have looked at the time taken for a DCR using different approaches and techniques and it has become obvious that the time taken is influenced by the experience of the surgeon and the number of steps involved, which may vary with different approaches. 7,10 The current study evaluates and compares 2 powered instruments: mechanical burrs and ultrasonic emulsification, with regard to the time taken to perform superior osteotomy and complications during this step of PEnDCR.…”
mentioning
confidence: 99%
See 1 more Smart Citation